Form discrimination in a case of blindsight. - Trevethan, C; Sahraie, A; Weiskrantz, L (2007)
DB, the first extensively tested blindsight case, has demonstrated the ability to detect and discriminate a range of visual stimuli presented within his perimetrically blind visual field [Weiskrantz L. (1986). Blindsight: A case study and implications. Oxford: Oxford University Press]. After initial reports of basic form discrimination (Weiskrantz, 1986), it later emerged that this ability to discriminate single stimuli presented to the blind field was probably based on the discrimination of orientation cues [Weiskrantz, L. (1987). Residual vision in a scotoma. A follow-up study of 'form' discrimination. Brain, 110, 77-92]. Even so, DB found it impossible to make a 'same/different' discrimination for pairs of stimuli in the blind field (Weiskrantz, 1986). In the current study, DB's discrimination and identification of stimuli on the basis of their form was tested (in 2AFC and FR paradigms). We have demonstrated that DB could successfully identify outline low contrast images of objects, make successful 'same/different' discriminations for pairs of stimuli presented in his blind field and identify complex images (digital photographs) presented entirely within his cortically blind field. The results are discussed in relation to the issues of likely neuronal mediation, the potential for improvement in cases of blindsight and the potential relevance of these findings in relation to theories of normal visual perception.